Highly sensitive detection of the antibiotic ciprofloxacin by means of fiber enhanced Raman spectroscopy - Wolf, Sebastian; Frosch, Timea; Popp, Juergen; Pletz, Mathias W.; Frosch, Torsten (Molecules, 2019)
Sepsis and septic shock exhibit a rapid course and a high fatality rate. Antibiotic treatment is time-critical and precise knowledge of the antibiotic concentration during the patients’ treatment would allow individual dose adaption. Over- and underdosing will increase the antimicrobial efficacy and reduce toxicity. We demonstrated that fiber enhanced Raman spectroscopy (FERS) can be used to detect very low concentrations of ciprofloxacin in clinically relevant doses, down to 1.5 µM. Fiber enhancement was achieved in bandgap shifted photonic crystal fibers. The high linearity between the Raman signals and the drug concentrations allows a robust calibration for drug quantification. The needed sample volume was very low (0.58 µL) and an acquisition time of 30 s allowed the rapid monitoring of ciprofloxacin levels in a less invasive way than conventional techniques. These results demonstrate that FERS has a high potential for clinical in-situ monitoring of ciprofloxacin levels.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Antibiotics; Ciprofloxacin; Fiber enhanced Raman spectroscopy; Fiber sensing; Hollow core photonic crystal fiber; Photonic bandgap; Sepsis; Therapeutic drug monitoring; Ultrasensitive